2 - Enhancing Doctoral Supervision Practices in Africa: Reflection on the CARTA Approach - Fonn, Sharon; Ezeh, Alex; Egesah, Oma; Cole, Donald C.; Izugbara, Chimaraoke; Bondjers, Göran; Manderson, Lenore (Journal of Higher Education in Africa, 2022)
High quality research supervision is crucial for PhD training, yet it continues to pose challenges globally with important contextual factors impacting the quality of supervision. This article reports on responses to these challenges by a multi-institutional sub-Saharan Africa initiative (CARTA) at institutional, faculty and PhD fellow levels. The article describes the pedagogical approaches and structural mechanisms used to enhance supervision among supervisors of CARTA fellows. These include residential training for supervisors, and supervision contracts between primary supervisors and PhD fellows. The authors reflect on the processes and experiences of improving PhD supervision, and suggest research questions that CARTA and other training programmes could pursue in relation to PhD supervision in Africa and other lower- and middle-income countries.